Pengaruh Tingkat Pengangguran Terbuka Dan Rasio Gini Terhadap Pertumbuhan Ekonomi Di Provinsi Jawa Timur 2018–2023 - Berliana Berliana (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Abstract. This study aims to analyze the influence of the open unemployment rate and the Gini ratio on economic growth in East Java Province for the period 2018–2023. Economic growth is an important indicator in assessing community welfare and the effectiveness of regional development. The research method uses a quantitative approach with secondary data obtained from the East Java Central Statistics Agency. Data analysis was conducted using multiple linear regression with the help of SPSS software. The results of the study indicate that simultaneously, the open unemployment rate and the Gini ratio have a significant effect on economic growth with a contribution of 8.2%, while the remainder is influenced by other variables outside the model. Partially, the open unemployment rate has a negative and significant effect on economic growth, which means that the higher the unemployment rate, the lower the economic growth tends to be. Conversely, the Gini ratio has a positive and significant effect on economic growth, indicating that increasing income inequality is correlated with increased economic activity. These findings demonstrate the importance of local government policies in reducing unemployment and managing income inequality so that economic growth in East Java can be sustainable and inclusive. Keywords: Gini Ratio; East Java; Open Unemployment; Economic Growth.